Observation of angle-dependent mode conversion and mode hopping in 2D annular antidot lattice - Porwal, Nikita (Sci Rep, 2019)
We report spin-wave excitations in annular antidot lattice fabricated from 15 nm-thin Ni(80)Fe(20) film. The nanodots of 170 nm diameters are embedded in the 350 nm (diameter) antidot lattice to form the annular antidot lattice, which is arranged in a square lattice with edge-to-edge separation of 120 nm. A strong anisotropy in the spin-wave modes are observed with the change in orientation angle (ϕ) of the in-plane bias magnetic field by using Time-resolved Magneto-optic Kerr microscope. A flattened four-fold rotational symmetry, mode hopping and mode conversion leading to mode quenching for three prominent spin-wave modes are observed in this lattice with the variation of the bias field orientation. Micromagnetic simulations enable us to successfully reproduce the measured evolution of frequencies with the orientation of bias magnetic field, as well as to identify the spatial profiles of the modes. The magnetostatic field analysis, suggest the existence of magnetostatic coupling between the dot and antidot in annular antidot sample. Further local excitations of some selective spin-wave modes using numerical simulations showed the anisotropic spin-wave propagation through the lattice.